Gender Differences in Language Use in Talks at Google (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This study examines the linguistic features utilised by male and female native English speakers during their Talks at Google using Lakoff and Lakoff’s framework of women’s language. The analysis is conducted on a sample of 14 videos, consisting of seven for each gender, using a mixed-method approach. The quantitative analysis presents the frequencies of the utterances used by the speakers, while the qualitative analysis identifies the language forms employed by each gender. The findings reveal that both genders employed the linguistic features suggested by Lakoff in their talks. Contrary to Lakoff and Lakoff’s assumptions, the female speakers utilised fewer linguistic features, accounting for only 47.43% of the features present in the corpus. Specifically, female speakers used intensifiers, tag questions and humour more frequently than male speakers, while male speakers employed empty adjectives, hedges, hypercorrect grammar and super polite forms more often than female speakers. The results provide insights into the language usage patterns of each gender and allude to possible changes in women’s use of linguistic patterns.